Peningkatan Kinerja Industri Manufaktur di Indonesia Melalui Penurunan High Cost Economy Periode 1990-2003 - Gitaharie, Beta Yulianita; Mardanugraha, Eugenia; Nuryakin, Chaikal; Suraya, Suraya (Jurnal Ekonomi dan Pembangunan Indonesia, 2007)
The economic crises attacking Asian regions in the mid of /997 have brought depressing impacts to Indonesia's economy. Indonesia experiences a declining share of investment- it is even the lowest amongst neighboring countries. Indonesia also ranks the first position in the issue of inefficiency which further discourages investors to invest in Indonesia. The study focuses on the issue of efficiency in the manufacturing industry whose share in the economy tends to increase during 1988-2005 in a higher percentage than in the agriculture and services sectors. The objectives of the study are two-folds, first is to measure the score ofefficiency in the manufacturing industry in order to identify which in industries are classified as efficient, moderately efficient, or less efficient. Secondly is to identify whether there is an association between input factor or output degree ofprotection and the score of inefficiency ofa 5-digit-ISIC industry. The method employs in the study is the stochastic production frontier where efficiency is an explicit function ,of specifically determining factors. The study finds that wood preservative industry has the highest efficiency score, while garment and textile industry has the lowest. The study also discovers there are more industries with less and moderately efficient classification. Sources of inefficiency are from the high output tariffs, which have potential contributions to high price and less competitive products in the market. The study recommends that manufacturing industries with low scores of efficiency should improve their productivities through lower cost of production. The government has to make effort to reduce tariff for finished goods. Taxes on luxurious goods and duty charges for export oriented industries should be eliminated as an alternative to increase efficiency in the manufacturing industry. Comparative advantages, particularly for linkage industries, should be improved.